A Semiotics Analysis of Forget Me not A Film Directed by Kei Horie Using Roland Barthes’ Theory - Esther Nauli -; Hot Saut Halomoan (e-LinguaTera, 2021)
Semiotics is the theory and study of signs and symbols, especially as elements of language or other systems of communication which include traffic signs, emojis, and emoticons used in electronic communication, and logos and brands used by international corporations to sell us things—"brand loyalty," they call it. This research is about semiotic analysis that presents the result from the research of signs in a film. The data the signs in Forget Me Not film that was downloaded from youtube.com. This research uses the semiotics theory of Roland Barthes that discusses the denotative meaning and the connotative meaning. The writer also used an online dictionary to find the definition. This is a qualitative research paper. The writer found the denotative meaning of a necklace is a jewelry with pendant. The connotative meaning of a necklace is to strengthen the relationship. The denotative meaning of a video showing living things to keep precious memories. It denotes that a picture is a thing that is based on an object. The writer concludes that the last connotative meaning of a picture is documenting the story